Strategies for Developing Transition Metal Phosphides in Electrochemical Water Splitting - Ying, Jie; Wang, Huan (Frontiers in Chemistry, 2021)
Electrochemical water splitting involving hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) is a greatly promising technology to generate sustainable and renewable energy resources, which relies on the exploration regarding the design of electrocatalysts with high efficiency, high stability, and low cost. Transition metal phosphides (TMPs), as nonprecious metallic electrocatalysts, have been extensively investigated and proved to be high-efficient electrocatalysts in both HER and OER. In this minireview, a general overview of recent progress in developing high-performance TMP electrocatalysts for electrochemical water splitting has been presented. Design strategies including composition engineering by element doping, hybridization, and tuning the molar ratio, structure engineering by porous structures, nanoarray structures, and amorphous structures, and surface/interface engineering by tuning surface wetting states, facet control, and novel substrate are summarized. Key scientific problems and prospective research directions are also briefly discussed.